Inhibitory activity of several extract of Piper betle Leaf against S. aureus - Ahmad Shobrun Jamil; Siti Rofida; Dinda Farida; Dwi Retno Nur Syahida; Trimianti Hidahyatun Nazah (Pharmaciana, 2021)
A high number of infections from year to year require infectious diseases to get serious attention. The antimicrobial compound exploration must be continued to anticipate the development of infectious diseases. The purpose of this study was to find out in vitro antimicrobial activity of n-hexane, ethyl acetate, and ethanol fractions of Piper betle green leaves against S. aureus, and profiles of secondary metabolite compounds contained in these three extracts. The antimicrobial activity test was carried out by disk diffusion test of the fraction of n-hexane, ethyl acetate, and ethanol at a concentration of 6,25, 12,5, and 18,75 Âµg/disk. Detection of secondary metabolite content was done by the Thin Layer Chromatography method with stain-view reagents. The highest antimicrobial activity was found in the ethyl acetate fraction and was significantly different from the activity in the ethanol and n-hexane fractions. However, the antibacterial activity of all fractions was lower compared to the positive control of amoxiclav 30Âµg/disk. The phytochemical screening results of secondary metabolites of each fraction were shown that the n-hexane fraction contained alkaloids, terpenoids, flavonoids, polyphenols, and anthraquinone; the ethyl acetate fraction contained terpenoids, polyphenols, and anthraquinone; while the ethanol fraction contained alkaloids, terpenoids, polyphenols, and anthraquinone. Based on the test results, it is concluded that all fractions of Piper betle leaf extract had high antimicrobial activity; meanwhile, the ethyl acetate fraction had the highest activities among others. Each fraction was proven to have a different composition of secondary metabolites.